ANALYSIS OF POLITENESS LANGUAGE STRATEGIES USED BY MADIUNESE IN FORUM MAHASISWA MADIUN MALANG (FORMADIMA) - RIZEKI, MUHAMMAD FAIZAL (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: language, politeness strategies, positive politeness, negative politeness,madiunese, formadima. Language has a social function as a tool to make a connection among human beings. In using language strategies such as Politeness, it affords us to become more eligible on using the choices that are made in language use. Madiunese as the object of the study, they have unique temperaments that differ from Solonese and Surabayanese culture characteristics. In conducting the study, the researcher analyzed two problems of study, as follows; (1) What are the positive politeness and negative politeness categories used in the conversations between Madiunese in Formadima, and (2) What is the possible reason on performing positive politeness and negative politeness categories within the conversation used by Madiunese speakers in Formadima. In this study, main theory to conduct the problems of study is using politeness strategies by Brown and Levinson (1987, p.101-210) which is also supported by the theory of Watts (2003).This study used qualitative analysis since the data of this study are conversations analysis and human social phenomena happened in Formadima by the members. In conducting this study, the researcher chooses and explains utterances based on the conversations containing positive politeness and negative politeness strategies. From 62 utterances on total of five conversations that have been analyzed by the researcher, there are 12 utterances containing positive politeness strategies and10 utterances categorized in negative politeness strategies.Based on the analysis of positive politeness strategies, the researcher finds two categories that used by the speakers, there are; (1) Claim Common Ground, and (2) Fulfill that the Hearer Wants Some X. In negative politeness, most of Madiunese used to be more careful when produced the utterances. The researcher finds negative politeness strategies that performed by Madiunese, namely; apologize, be pessimistic,and sometimes go on record or baldly to indebting the hearers.Finally, the researcher suggests for further study about politeness should be conducted properly according to the object e.g., daily conversations or another human social phenomena which can be acquired in many things on social terms. Theresearcher also suggests to the next researchers to use other theories related topoliteness in analyzing the implicit meaning of the utterances produced by the speaker.